Surviving in the Brine: A Multi-Omics Approach for Understanding the Physiology of the Halophile Fungus Aspergillus sydowii at Saturated NaCl Concentration - Jiménez-Gómez, Irina; Valdés-Muñoz, Gisell; Moreno-Ulloa, Aldo; Pérez-Llano, Yordanis; Moreno-Perlín, Tonatiuh; Silva-Jiménez, Hortencia; Barreto-Curiel, Fernando; Sánchez-Carbente, María del Rayo; Folch-Mallol, Jorge Luis; Gunde-Cimerman, Nina; Lago-Lestón, Asunción; Batista-García, Ramón Alberto (Frontiers in Microbiology, 2022)
Halophilic Aspergillus sydowii is a model organism for the study of molecular adaptations of filamentous fungi to hypersaline conditions. For the first time an omics approach was used to compare A. sydowii at optimal salinity (1 M NaCl) to saturated concentration (5.13 M NaCl). At saturation, 1.842 genes were differentially expressed of which 704 were overexpressed. GO analysis showed significant enrichment of 26 biological processes, 26 molecular functions, and four cellular components. Most differentially expressed genes were involved in metabolism and signal transduction. ATP binding constituted the main network node with direct interactions to phosphorelay signal transduction, polysaccharide metabolism and transferase activity. Free amino acids significantly decreased and amino acid metabolism was reprogrammed. mRNA transcriptional analysis revealed upregulation of genes involved in methionine and cysteine biosynthesis. No modifications of membrane fatty acid composition occurred. Upregulated genes were involved in high-osmolarity glycerol signal transduction pathways, biosynthesis of beta-1,3-glucans and cross membrane ion transporters. Downregulated genes were related to the synthesis of chitin, mannose, cell wall proteins, starvation, pheromone synthesis and cell cycle. 20% of transcripts were classified as non-coding RNA with 7% classified as lncRNAs. 42% and 69% of the total lncRNAs and RNAs encoding transcription factors were differentially expressed. Three clusters of differentially expressed mRNAs were related to metabolic processes, protein phosphorylation, protein kinase activity and plasma membrane composition. Metabolomic analyses revealed more complex and unknown metabolites at saturated NaCl concentration than at optimal salinity. This study is the first attempt to unravel the ecology of an ascomycete fungus at saturated NaCl.